TRANSAXILLARY ENDOVIDEOSURGICAL ACCESS IN THYROID SURGERY - D. Yu. Semenov; M. E. Boriskova; P. A. Pankova; G. V. Volchkov; M. A. Bykov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study is to analyze the results of practical application of endovideosurgical transaxillary access in thyroid surgery. MATERIAL AND METHODS. We performed the retrospective comparative analysis of the results of surgical treatment of thyroid diseases using traditional, Miccoli’s endovideo-assisted access, endovideosurgical transaxillary access. RESULTS. With the use of endovideosurgical transaxillary access, the best cosmetic result is achieved – the absence of a scar on the neck. The number of specific complications in the samples is not significantly different, nonspecific complications are not accompanied with functional disorders. CONCLUSION. The expediency of improving the endovideosurgical thyroid surgery from remote accesses showed demand ability and safety of the technique. The important condition for their application is the possibility of performing an operative intervention in a proper manner.